Haptic Aesthetics as the Possibility of Haptic Epistemology - Maša Tomšič (ESPES)
The denotative and theoretical indeterminacy make the sense of touch an ambiguous concept to work with. While materiality and relationality, traditionally assigned in philosophical discourses and acknowledged through scientific research, are considered as the inherent dimensions of touch, the paper additionally proposes ambiguity as one of its integral traits. The notion of ambiguity, which encapsulates the tension between contrasting notions in both, the conceptualizations of touch as well as the touch-derived phenomenological experiences, is suggested as epistemologically generative, and a vital condition for sensory knowing, especially in aesthetics. This represents the basis for discussing the significance of a non-discursive haptic epistemology in outlining haptic aesthetics and aesthetic experience, which are marked by the necessary openness and inconclusiveness, required for the particular epistemic potential of art.